ADAPTING LEADERSHIP STYLE FOR FLEXIBLE WORK ENVIRONMENT: A REVIEW OF LITERATURE - Priya; Sinha, Neha; Modanwal, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose-The rise of flexible work environments, characterized by remote work, flexible hours, and decentralized teams, has fundamentally transformed traditional organizational structures and leadership paradigms. The study explores the necessity for leaders to adapt their leadership styles to effectively manage and guide teams within these dynamic and fluid work settings. Through a systematic literature review of leadership theories and flexible work arrangements, including transformational, transactional, and situational leadership, this study examines how various leadership approaches can be modified to meet the demands of a flexible workforce. The study also focuses on how leaders can maintain team cohesion and performance and faces the challenges in managing remote or hybrid teams. Design/Methodology- This study systematically reviews, synthesizes and integrates literature using the well-recommended preferred reporting items for systematic reviews and meta-analyses (PRISMA) rules. Findings- The findings underscore the importance of an empowering, participative, transformational, transactional ethical leadership approach that is responsive to the unique challenges and opportunities presented by flexible work environments, ultimately contributing to the success and sustainability of organizations in the modern era. It has also been identified that major work on leadership approaches in flexible work setting has been done in between 2022-2024. By integrating and critically analyzing empowering, participative, transformational, transactional, and ethical leadership styles, the study offers a comprehensive framework for navigating the complexities of modern work environments. Originality/ Value of the Paper- This research is invaluable as it builds upon and synthesizes the significant body of work on leadership approaches in flexible work settings. It highlights the relevance of adaptive leadership styles in hybrid or remote work environment and suggests that it has been undervalued in research to date. Irrespective of the specific areas of interest of different studies, there is a growing need for a more comprehensive understanding of the adaptive leadership and their influence on team cohesion and team performance. The findings provide actionable insights for leaders seeking to foster innovation, employee engagement, and organizational resilience, making it a crucial contribution to both academic discourse and practical leadership strategies in an era of rapid workplace transformation.